2020
DOI: 10.5851/kosfa.2020.e44
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Comparative Evaluation of Milk Protein Variants from Pakistani Dairy Breeds

Abstract: The aim of study was to scrutinize the physicochemical and protein profile of milk obtained from local Pakistani breeds of milch animals such as Nilli-Ravi buffalo, Sahiwal cow, Kajli sheep, Beetal goat and Brela camel. Physicochemical analysis unveiled maximum number of total solids and protein found in sheep and minimum in camel. Buffalo milk contains the highest level of fat (7.45%) while camel milk contains minimum (1.94%). Ash was found maximum in buffalo (0.81%) and sheep (0.80%) while minimum in cow’s m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 39 publications
2
5
1
Order By: Relevance
“…The major whey protein observed in CM and GM is ⊍-LA and they did not contain quantifiable amounts of ⊎-Lg. The findings were similar to those observed by Yasmin et al 23 Both cattle and non-cattle hydrolysates had bands lesser than 14 kDa, which were not visible, indicating the presence of low molecular-weight peptides produced as a result of alcalase hydrolysis of larger proteins and corroborated the observations of DH.…”
Section: Tricine Sds-page Of Different Skimmed Milk Proteinssupporting
confidence: 90%
“…The major whey protein observed in CM and GM is ⊍-LA and they did not contain quantifiable amounts of ⊎-Lg. The findings were similar to those observed by Yasmin et al 23 Both cattle and non-cattle hydrolysates had bands lesser than 14 kDa, which were not visible, indicating the presence of low molecular-weight peptides produced as a result of alcalase hydrolysis of larger proteins and corroborated the observations of DH.…”
Section: Tricine Sds-page Of Different Skimmed Milk Proteinssupporting
confidence: 90%
“…In this work, the hemolytic activity was negative in all the isolates. This result is coincided with (Oh and Jung 2015;Yasmin et al 2020). Such strains are non-virulence and lack hemolysin confirmed that the virulence does not appear among the bacterial strains (FAO/WHO 2006).…”
Section: Discussionsupporting
confidence: 61%
“…In this work, the hemolytic activity was negative in all the isolates. This result is coincided with (Oh and Jung 2015;Yasmin et al 2020). Such strains are nonvirulence and lack hemolysin con rmed that the virulence does not appear among the bacterial strains (FAO/WHO 2006).…”
Section: Discussionmentioning
confidence: 62%